Study on dynamic behaviour of wishbone suspension system - M., Kamal; M. M., Rahman (IOP Publishing, 2012)
This paper presents the characteristic model of the wishbone suspension system using the quarter car model approach. Suspension system in an automobile provides vehicle control and passenger comfort by providing isolation from road disturbances. This makes it essential that the detailed behavior of suspension should be known to optimize the performance. A kinetic study is performed using multi body system (MBS) analysis. The dirt road profile is considered as an applied loading. The spring constant, damping coefficient and sprung mass are studied on the performance of the suspension system. It can be observed that the spring constant is inversely related with time required to return to initial position and the amount of deformations. The damping ratio affects the suppression of spring oscillations, beyond a certain limit damping ration has the negligible effect. Sprung mass effected the equilibrium position of the suspension system with a small effect on its oscillation behavior. It is shown that the spring constant, damping ratio and sprung mass are significant parameters to design the suspension system. This study is essential for complete understanding of working of the suspension system and a future study with real geometries.